Immunotherapy in Hepatocellular Carcinoma (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Based on this evidence, a deep understanding of the immunological status and biological targets modulating immunological microenvironments should be quite informative for the development of future immunotherapy in HCC. From this point of view, this Special Issue will highlight the current state of the art in the immunotherapy of HCC from both the basic and clinical perspectives, and outline future perspectives for improving therapies.